Output Stabilization of Infinite Dimensional Bilinear Systems with Delayed Observation - Kazoui, Khalil EL; Ezzaki, Hassan; Boulouz, Abed (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we are concerned with the output stabilization of infinite dimensional bilinear systems with delayed observation. We first establish the well-posedness of such systems and then we provide sufficient conditions for strong and weak output stabilization. Through the analysis of the wave equation and beam equation, we demonstrate the applicability and effectiveness of our proposed methods.